Gender regimes, citizen participation and rural restructuring - Asztalos Morell, Ildikó; Bock, Bettina B. 1960- (Research in rural sociology and development, 2008)
This volume looks at the construction of gendered citizenship in different rural contexts. These contexts represent different welfare state and gender regimes, and different rural/agricultural conditions as characterized in different countryside types. This is a study of gender, citizenship and gender regimes, in a rural context with an international list of contributors.